Spontaneous Complete Remission in a Patient with Acute Myeloid Leukemia and Severe Sepsis - Rambod Mozafari; Mahsa Moeinian; Ali Asadollahi-Amin (Case Reports in Hematology)
Without treatment, acute myeloid leukemia (AML) is almost always fatal. Spontaneous remission of AML is a rare phenomenon and usually with a short duration. The exact mechanisms are unknown. However, its association with infection and blood transfusions has been described. We report a 53-year-old male who presented with severe sepsis and who was diagnosed with AML (M4). He has experienced complete spontaneous remission with relatively long duration. To the best of our knowledge, it is the first case of spontaneous remission described in Iran.